2010
DOI: 10.1007/s00404-010-1596-9
|View full text |Cite|
|
Sign up to set email alerts
|

Bone mineral density changes in pregnancies with gestational hypertension: a longitudinal study using quantitative ultrasound measurements

Abstract: ObjectiveTo compare the maternal bone mineral density (BMD) changes in gestational hypertensive and normotensive pregnancies using quantitative ultrasound.MethodsConsecutive patients were recruited from a general obstetric clinic over a period of 9 months. BMD measurements were performed at the os calcis in early pregnancy before 20 weeks and in the late third trimester after 36 weeks, using a Hologic Sahara Clinical Bone Sonometer system. These patients were followed up in accordance with standard antenatal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…First, the vertebral total vBMD did not vary by pregnancy history in women 35 years after the index pregnancy. This finding is consistent with those of shorter-term prospective, observational studies that found no differences in areal BMD as measured using bone ultrasound at the heel at 14–20 and 36–38 weeks during the pregnancy among women with normotensive, gestational hypertension or preeclamptic pregnancies and DEXA at the femur and lumbar spine within two days after delivery (12, 19). Thus, the current study extends these observations to 35 years after the index pregnancy.…”
Section: Discussionsupporting
confidence: 90%
“…First, the vertebral total vBMD did not vary by pregnancy history in women 35 years after the index pregnancy. This finding is consistent with those of shorter-term prospective, observational studies that found no differences in areal BMD as measured using bone ultrasound at the heel at 14–20 and 36–38 weeks during the pregnancy among women with normotensive, gestational hypertension or preeclamptic pregnancies and DEXA at the femur and lumbar spine within two days after delivery (12, 19). Thus, the current study extends these observations to 35 years after the index pregnancy.…”
Section: Discussionsupporting
confidence: 90%
“…During pregnancy, maternal bone mineral density (BMD) and bone resorption markers are modestly increased [21,22,42,47]. With increased number of pregnancies, we hypothesize that the BMD and phosphorus and calcium bioavailability is reduced.…”
Section: Discussionmentioning
confidence: 97%
“…Studies show that bone turnover biochemical markers increase in pregnancies complicated by preeclampsia [20]. Interestingly enough, although maternal bone mineral density (BMD) is unaffected by preeclampsia [21,22], adult offspring who were previously exposed to maternal preeclampsia in the womb present higher BMD levels than those not exposed [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, whereas one study (Hannam et al, 2015) shows a modest but significant negative association of maternal pre-eclampsia and hip and total body bone mineral density in adolescent offspring, another paper (Miettola et al, 2013) reports a protective effect of maternal pre-eclampsia on lumbar spine, femoral neck, and whole body bone mineral density in young-adult offspring born preterm at very low birth weight (< 1500 g), and likely also among those born at term not being small for gestational age. A third study (To and Wong, 2011) failed to find any significant association between gestational hypertensive disorders and offspring's bone mineral density measured at the os calcis before 20 weeks and after 36 weeks of pregnancy.…”
mentioning
confidence: 93%